2021
DOI: 10.1002/ar.24849
|View full text |Cite
|
Sign up to set email alerts
|

You can't keep a bad idea down: Dark history, death, and potential rebirth of eugenics

Abstract: “Be careful what you wish for”: This adage guides both how this project came to life, and how the topic covered in this review continues to unfold. What began as talks between two friends on shared interests in military history led to a 4‐year discussion about how our science curriculum does little to introduce our students to societal and ethical impacts of the science they are taught. What emerged was a curricular idea centered on how “good intentions” of some were developed and twisted by others to result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 299 publications
(639 reference statements)
0
7
0
Order By: Relevance
“…Despite the public belief that eugenics disappeared with the defeat of the Third Reich, scholars have shown that eugenic thought mutated into new forms. Postwar eugenic ideas were seldom expressed in term of coercive governmental action and eugenic advocates often framed their ideas in terms of voluntary measures that would prevent genetic deterioration of future generations (Duster, 2003;Ladd-Taylor, 2001;Largent, 2008;Liscum & Garcia, 2022;Mazumdar, 2002;Ramsden, 2009). Jensen's eugenic ideas reflected this kinder, gentler eugenics.…”
Section: Jensen's Politics: Eugenicsmentioning
confidence: 99%
“…Despite the public belief that eugenics disappeared with the defeat of the Third Reich, scholars have shown that eugenic thought mutated into new forms. Postwar eugenic ideas were seldom expressed in term of coercive governmental action and eugenic advocates often framed their ideas in terms of voluntary measures that would prevent genetic deterioration of future generations (Duster, 2003;Ladd-Taylor, 2001;Largent, 2008;Liscum & Garcia, 2022;Mazumdar, 2002;Ramsden, 2009). Jensen's eugenic ideas reflected this kinder, gentler eugenics.…”
Section: Jensen's Politics: Eugenicsmentioning
confidence: 99%
“…As such, there is a danger that overly prescriptive AI diagnostics may further hinder students' uncertainty tolerance, giving them a flattened sense of the ambiguities and uncertainties intrinsic in human anatomy. Anatomical education has progressed over the past 20 years to better reflect the clinical relevance of human anatomical variation (Willan & Humpherson, 1999; Wheble & Channon, 2021; Cullinane & Barry, 2022), and is now calling into question historical and contemporary anatomical representations that fail to consider differences based on race, skin tone, sex, gender, body type, and age (Liscum & Garcia, 2022; Easterling & Byram, 2022; Finn et al, 2022; Smith, 2022). Artificial intelligence‐infused anatomical education does not currently support this diversity of the human form robustly.…”
Section: Weaknesses and Threats With Artificial Intelligence‐infused ...mentioning
confidence: 99%
“…Racism is perpetuated through both interpersonal and institutional practices” (Race‐website, 2022). Racial categorization in European contexts became prominent during the Enlightenment (17th and 18th centuries) starting with Carolus Linnaeus (Hudson, 1996; Liscum & Garcia, 2022; Figure 1b). He inscribed upon the natural world the notions Europeans held at the time, launching the system that led to the “biologicalization” of race.…”
Section: Broader Scientific Context In Which the Aaa Formed And Devel...mentioning
confidence: 99%